Agility Marketing: Improving Marketing Performance with Customer Responsiveness, High Flexibility, Human Collaboration, and Continuous Improvement - Verawaty Verawaty (International Journal of Artificial Intelligence Research, 2022)
This study aims to identify the relationship between the dimensions of agility marketing which include responsiveness to customers, high flexibility, human collaboration, and continuous improvement to improve marketing performance in the company. This research uses quantitative methods by collecting data through questionnaires distributed to respondents who work in marketing in the company. The total respondents taken were 150 people. The data were then analyzed using correlation techniques and SWOT analysis. The results showed that the four dimensions of agility marketing, namely responsiveness to customers, high flexibility, human collaboration, and continuous improvement, were positively and significantly related to marketing performance in the company. Responsiveness to customers and continuous improvement have the greatest contribution to improving marketing performance. This research shows that companies that implement agility marketing principles well will have better marketing performance. Responsiveness to customers and continuous improvement have a very important role in improving marketing performance in the company. Therefore, companies should focus on developing strategies that are able to increase responsiveness to customers and improve marketing performance continuously.